D9.13 Report on the organisation of the annual ECoE International Workshop (RP1), WP9 - Loulli, Eleni; Prodromou, Maria; Papoutsa, Christiana; Tzouvaras, Marios; Hadjimitsis, Diofantos G. (My University, 2020)
The consortium of the EXCELSIOR Project and the Eratosthenes Centre of Excellence organised a heavily publicised virtual workshop with the participation of all national, EMMENA and international stakeholders. The workshop, which will be organised annually, addressed all the different activities of the Eratosthenes Centre of Excellence, i.e., infrastructure, research, education and innovation through entrepreneurship. The intention was that this Workshop would coincide with the Annual International Conference on Remote Sensing and Geo-information of Environment, but due to the COVID-19 pandemic restrictions the 2020 conference was cancelled. Thus, the workshop was postponed for the 15th of July and was held virtually using an online platform. The workshop aimed in strengthening regional links, investing in the continuous interaction with the strategic user segments of the Eratosthenes Centre of Excellence and sustaining long-lasting relationships and partnerships in the region. The Cyprus University of Technology led the organization of this workshop, while all EXCELSIOR Project partners contributed.